High Blocking Temperature of Magnetization and Giant Coercivity in the Azafullerene Tb2@C79N with a Single‐Electron Terbium–Terbium Bond. Issue 18 (27th March 2019) - Velkos, Georgios; Krylov, Denis S.; Kirkpatrick, Kyle; Spree, Lukas; Dubrovin, Vasilii; Büchner, Bernd; Avdoshenko, Stanislav M.; Bezmelnitsyn, Valeriy; Davis, Sean; Faust, Paul; Duchamp, James; Dorn, Harry C.; et al.
Abstract: The azafullerene Tb2 @C79 N is found to be a single‐molecule magnet with a high 100‐s blocking temperature of magnetization of 24 K and large coercivity. Tb magnetic moments with an easy‐axis single‐ion magnetic anisotropy are strongly coupled by the unpaired spin of the single‐electron Tb−Tb bond. Relaxation of magnetization in Tb2 @C79 N below 15 K proceeds via quantum tunneling of magnetization with the characteristic time τ QTM =16 462±1230 s. At higher temperature, relaxation follows the Orbach mechanism with a barrier of 757±4 K, corresponding to the excited states, in which one of the Tb spins is flipped. Abstract : New kids on the blocking : The azafullerene Tb2 @C79 N featuring a single‐electron Tb−Tb bond is found to be an air‐stable single‐molecule magnet with a high 100‐s blocking temperature of magnetization of 24 K and large coercivity. Tb magnetic moments with an easy‐axis single‐ion magnetic anisotropy are strongly coupled by the unpaired spin of the single‐electron Tb−Tb bond.